Boundary engineering of porous zinc oxide nanosheets to enhance gas sensing performance - Min Young Kim; Haeun Choa; Chul Oh Park; Dung Thi Hanh To; Tran Khanh Phuong Cao; Emily Resendiz Mendoza; Changhyun Jin; Beom Zoo Lee; Nosang Vincent Myung; Kyu Hyoung Lee (Sensors and Actuators Reports)
Zinc oxide (ZnO) based gas sensors are noted for their high sensing response toward a wide range of gases, however, they often face challenges in achieving other required properties due to complex reaction dynamics under different operating conditions. Herein, we fabricated boundary-engineered porous ZnO nanosheets by controlling calcination temperature of hydrozincite. These materials were systematically evaluated their sensing performance towards oxidizing gases, reducing inorganic gases, and volatile organic compounds. Additionally, detailed sensing properties toward NO2, NH3, and acetone were examined to investigate the critical roles of the energy barrier for carrier transport (Eb) and the nature of ionized oxygen species in the sensing materials. Characteristics of the materials, such as crystallite size, pore size, porosity, and surface area, were effectively tuned, which significantly influenced Eb and sensing performance. The porous ZnO nanosheets calcined at 300 °C for 4 h, exhibiting a higher density of boundaries, demonstrated enhanced sensing performance with maximum response values of 10.59 for NO2, 0.38 for NH3, and 0.41 for acetone at personnel exposure level. This improvement is likely linked to the increased surface charge carrier concentration and the higher Eb associated with greater boundary density, indicating an increase in available reaction active sites. Furthermore, our findings reveal that gas sensing behavior is strongly dependent on the type of ionized oxygen species present. The optimal sensing temperature for NO2 is 250 °C, where the dominant ionized oxygen species is O−, while for NH3 and acetone, the optimal temperature was 450 °C, where O2− is the predominant species.